2019
DOI: 10.1051/0004-6361/201832860
|View full text |Cite
|
Sign up to set email alerts
|

Consistent dust and gas models for protoplanetary disks

Abstract: Context. Consistent modeling of protoplanetary disks requires the simultaneous solution of both continuum and line radiative transfer, heating and cooling balance between dust and gas and, of course, chemistry. Such models depend on panchromatic observations that can provide a complete description of the physical and chemical properties and energy balance of protoplanetary systems. Along these lines, we present a homogeneous, panchromatic collection of data on a sample of 85 T Tauri and Herbig Ae objects for w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 157 publications
0
23
0
Order By: Relevance
“…Interestingly, Labdon et al (2019) found that the location of the inner disk of SUAur is similarly controlled by the sublimation of 0.40 μm grains while Davies et al (2018) found that larger (1.2 μm) grains were required to reproduce their Hand K-band interferometric observations of HD142666. Both SUAur and HD142666 are similar in mass (~M 2  ) to RY Tau, while HD142666 is older (>10 Myr; Dionatos et al 2019) and more luminous (~L 20 ;…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly, Labdon et al (2019) found that the location of the inner disk of SUAur is similarly controlled by the sublimation of 0.40 μm grains while Davies et al (2018) found that larger (1.2 μm) grains were required to reproduce their Hand K-band interferometric observations of HD142666. Both SUAur and HD142666 are similar in mass (~M 2  ) to RY Tau, while HD142666 is older (>10 Myr; Dionatos et al 2019) and more luminous (~L 20 ;…”
Section: Discussionmentioning
confidence: 92%
“…For our determination we took the data from the DIANA database (Dionatos et al 2019) and their resulting model fit, which matches excellently these data points. We interpolated the points to obtain an SED with constant d logλ steps with a step size of 0.01, which is about the average spacing of available data points.…”
Section: Spectral Energy Distributionmentioning
confidence: 88%
“…The dust temperature in the disk is calculated using the radiative transfer code RADMC-3D (Dullemond et al 2012). The input UV and X-ray spectra of TW Hya are taken from Dionatos et al (2019), and they are added to a Black body component with the effective temperature of 4110 K (Andrews et al 2012). The local UV radiation and X-ray radiation fields inside the disk are also calculated with RADMC-3D, considering both absorption and scattering.…”
Section: Model Descriptionmentioning
confidence: 99%